II Certamen Crono-Teatro (2014). Modalidad de andén 3. Las tijeras de Miller - Pygmalión (Pygmalion. Revista de teatro general y comparado, 2025)
II Certamen Crono-Teatro (2014). Modalidad de andén 3. Las tijeras de Miller